Agro-economic-industrial Economy of India and Sustainable Development in WTO Regime - Kaur, Harmeet (Journal of Commerce and Trade, 2016)
India is primarily the country of villages. And, most of the village-population depends largely upon the agricultural activities. Moreover, the rest of the population, also, relates with such agricultural activities, directly and indirectly. On the other hand, if we see in a big perspective, the population in the urban areas is also depending on agriculture and related sources of earnings. This way, country’s maximum development goes through the development of agriculture and related source of earnings. India made significant advances towards achieving its goals of rapid agricultural growth, improving food security, and reducing rural poverty during the last four decades. Sustained food grain production growth enabled India to achieve food grain, self-sufficiency, eliminating the threat of famines and acute starvation in the country. These changes will improve the investment climate for farmers and the private sector to effectively meet market opportunities.